2020
DOI: 10.1111/jam.14803
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screening and characterization of bacteria associated with hospital cockroaches ( Blattella germanica L.) using MALDI‐TOF mass spectrometry

Abstract: Aims The study aimed to explore the diversity of culturable microbiota colonizing the alimentary tract and outer surfaces of German cockroaches (Blattella germanica) captured in a health care facility. Methods and Results Microbial identification was conducted using Matrix Assisted Laser Desorption–Ionization Time‐of‐Flight Mass Spectrometry (MALDI‐TOF MS) Biotyper and 16S rRNA sequencing. A total of 181 bacteria strains were isolated from 25 cockroach specimens and the MALDI‐TOF MS‐based assay yielded direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Further, the detailed analysis of the microbiome and the resistome of Blattella germanica populations fed with added faeces to their diet showed the presence of mobile elements and ARGs in their metagenomes ( Domínguez-Santos et al., 2021 ). Furthermore, it has been described that those cockroaches captured in health care facilities present in their gut a high prevalence of the pathogens circulating in said facilities ( Mehainaoui et al., 2021 ). Other animals co-existing with humans, such as rats, flies or fleas, known to be involved in the transmission of life-threatening infectious diseases, might also contribute to the horizontal transfer of ARGs among different pathogens.…”
Section: The Role Of Wildlife In the Origin And The Horizontal Transf...mentioning
confidence: 99%
“…Further, the detailed analysis of the microbiome and the resistome of Blattella germanica populations fed with added faeces to their diet showed the presence of mobile elements and ARGs in their metagenomes ( Domínguez-Santos et al., 2021 ). Furthermore, it has been described that those cockroaches captured in health care facilities present in their gut a high prevalence of the pathogens circulating in said facilities ( Mehainaoui et al., 2021 ). Other animals co-existing with humans, such as rats, flies or fleas, known to be involved in the transmission of life-threatening infectious diseases, might also contribute to the horizontal transfer of ARGs among different pathogens.…”
Section: The Role Of Wildlife In the Origin And The Horizontal Transf...mentioning
confidence: 99%
“…Hence, the increase in interest in the use of biopreservatives in foods to control their growth (Mechai et al, 2014). The antagonistic effect of L. plantarum SJ14 showed a broad spectrum of activity against Klebsiella pneumoniae, Escherichia coli, Enterobacter cloacae, and Salmonella Typhi, including extendedspectrum beta-lactamase-producing Enterobacteriaceae (ESBL), the most common responsible human pathogens (Mehainaoui et al, 2021). As far as it is known, antibacterial activity of bacteriocins from LAB against Gram-negative bacteria is an unusual phe- The obtained results (Table 2) indicated that the strain SJ14 is potential candidates for producing antifungal metabolites.…”
Section: Antibacterial and Antifungal Activitymentioning
confidence: 99%
“…Even though MALDI‐TOF/MS is fast, accurate, more accessible than molecular detection methods (Singhal et al, 2015), and widely used in studies to identify the microbiota of different arthropod species, such as bees (Kačániová et al, 2020; Praet et al, 2017), beetles (Perlatti et al, 2017; Wang & Rozen, 2017), cockroaches (Mehainaoui et al, 2021), and mosquitoes (Arruda et al, 2021; Barnard et al, 2019; Gonçalves et al, 2019; Tandina et al, 2016), it is worth mentioning that this approach may not be accurate enough for identifying nonclinical isolates, such as insect symbionts, since MALDI‐TOF databases are mainly focused on clinical specimens. The nonidentification of the 10 isolates abovementioned reflects this limitation of the technique, and additional tests, such as 16S‐ribosomal RNA sequencing, are required for more accurate detection of the cultivable microbiota of R. palmarum .…”
Section: Resultsmentioning
confidence: 99%